Peran Pemimpin Pembelajaran dalam Meningkatkan Hasil Belajar Siswa - Wahyudi, Ahmad; Sumardjoko, Bambang; Darsinah, D. (Jurnal VARIDIKA, 2019)
The purpose of this study is to describe the role of learning leadership and the obstacles faced by school principals in improving student learning outcomes at SMK Pelita Bangsa Sumberlawang Sragen. This research is a qualitative research that produces descriptive data in the form of words, written or oral from people and observed behavior. Data collection techniques carried out by in-depth interviews, observation, and documentation. Data analysis techniques using an interactive model of analysis. The results showed, first, the principal was the most instrumental element in improving the quality of education and learning. Learning leadership at SMK Pelita Bangsa Sumberlawang Sragen is carried out in 3 dimensions, namely through the formulation of school missions, good learning management, and building a conducive school climate. Second, the obstacles in implementing leadership learning in SMK Pelita Bangsa Sumberlawang Sragen include several things, namely the lack of professional teachers, conventional curriculum, incomplete supervision, and incomplete learning infrastructure.